PENGARUH AMICUS CURIAE TERHADAP PUTUSAN HAKIM MENURUT SISTEM PERADILAN PIDANA DI INDONESIA - Ronaldo Stefano; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Amicus Curie is a term that means "friend of the court" or what is known asFriend of the Court. Amicus curiae is filed by someone who is not a party involvedin a case in a judicial process. Amicus curiae is a way to provide an opinion, andnot to fight, but amicus curiae gives influence to the judge in ensuring additionalpoints of view and relevant information in his considerations. The judicial systemin Indonesia is not yet clearly regulated, but the legal basis for accepting amicuscuriae in Indonesia is in article 5 paragraph (1) of Law no. 48 of 2009 concerningjudicial power, which states that judges and constitutional justices are obliged toexplore, follow and understand the legal values and sense of justice that exist insociety. The aim of this research was to determine the influence of amicus curiae inthe criminal justice system and to find out the legal provisions for amicus curiae inthe future in the criminal justice system in Indonesia.This research is normative legal research supported by secondary data,carried out by using library materials as the main focus. Also called doctrinal legalresearch, namely legal research that uses data based on library research by takingquotations from reading books, or supporting books that are related to the problemto be researched. Thus, this research uses secondary data sources consisting ofprimary, secondary and tertiary legal materials. Thisresearch also uses qualitativedata analysis and produces descriptive data.The results of the study concluded that amicus curiae had an influence onjudges' decisions which had different results. In several decisions, the participationof the amicus curiae plays an important role in the judge giving the decision so thatthe opinions and views expressed influence the final outcome of the decision, but insome cases the amicus curiae is completely ignored for various reasons, one ofwhich isthat the defendants have fulfilled the elements of a criminal act so the judgedoes not accept the amicus curiae. This and amicus curiae require new, clearerregulations on criminal matters, which will make it easier for judges to expressopinions from amicus curiae into a decision.Keywords: Influence – Amicus curiae– Judge's decision.